The Role of Smallholder Farms in Food and Nutrition Security 2020
DOI: 10.1007/978-3-030-42148-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Global Change and Investments in Smallholder Irrigation for Food and Nutrition Security in Sub-Saharan Africa

Abstract: Investments in irrigation contribute to poverty reduction and enhance food security. This paper considers irrigation investments more broadly in the context of rural–urban linkages and thus examines rural irrigation schemes and peri-urban and urban agriculture using freshwater, groundwater and wastewater. We present case studies from East, West and Southern Africa, while focusing on the imperative of smallholders and of food security and nutrition. Evidence from Big Data and telecoupling show that, amid global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…From our survey work, we found that 2 out of 140 smallholders irrigated. However, some initiatives show promise in making irrigation feasible for smallholder farmers -for example, through public investments in South Africa, public-private partnerships in Zimbabwe, and SI business models in Tanzania (Hanjra and Williams, 2020). Whether irrigation is feasible also depends on regional water availability.…”
Section: Impact Of Minimum Si Measures On Cropland Esssmentioning
confidence: 99%
“…From our survey work, we found that 2 out of 140 smallholders irrigated. However, some initiatives show promise in making irrigation feasible for smallholder farmers -for example, through public investments in South Africa, public-private partnerships in Zimbabwe, and SI business models in Tanzania (Hanjra and Williams, 2020). Whether irrigation is feasible also depends on regional water availability.…”
Section: Impact Of Minimum Si Measures On Cropland Esssmentioning
confidence: 99%
“…Globally, smallholder irrigation schemes were developed to enhance the livelihoods of rural households (Mdemu et al, 2020), improve food security (Masasi and Ng'ombe, 2019), raise farm household income (Masasi and Ng'ombe, 2019), alleviate poverty (Phakathi, 2022), and agricultural transformation (Masasi and Ng'ombe, 2019). This development was predicted to be stimulated by high-impact pathways including higher crop yield, higher food production, and higher income (Hanjra and Williams, 2020). Nonetheless, there is abundant literature (Burney and Naylor, 2012;Fanadzo and Ncube, 2018;Hanjra and Williams, 2020;Mdemu et al, 2020) indicating that a majority of the smallholder irrigation schemes in SSA and especially in Zimbabwe have not performed according to the expectations as they are characterized by poor maintenance and dilapidated infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…This development was predicted to be stimulated by high-impact pathways including higher crop yield, higher food production, and higher income (Hanjra and Williams, 2020). Nonetheless, there is abundant literature (Burney and Naylor, 2012;Fanadzo and Ncube, 2018;Hanjra and Williams, 2020;Mdemu et al, 2020) indicating that a majority of the smallholder irrigation schemes in SSA and especially in Zimbabwe have not performed according to the expectations as they are characterized by poor maintenance and dilapidated infrastructure. According to Harrison (2018), farmer-led, externally engineered, and induced schemes models are more complex, costly, outdated, mismanaged, and have high failure rates.…”
Section: Introductionmentioning
confidence: 99%
“…The input of electricity provides a foundational building block upon which rural development becomes possible [44][45][46]. Reliable and sustainable electricity access enables pumping groundwater or stored rainwater, which when used for irrigation has significant potential for contributing to closing the yield gap [47][48][49]. For instance, Banerjee et al [23] estimate that by 2030 power demand from agriculture for both irrigation and milling in SSA could double from current levels if rainfed areas with economic potential would be equipped for irrigation, reaching about 9 GW.…”
Section: Introductionmentioning
confidence: 99%